Carbonized wood flour matrix with functional phase change material composite for magnetocaloric-assisted photothermal conversion and storage. (1st July 2020) - Chao, Weixiang; Yang, Haiyue; Cao, Guoliang; Sun, Xiaohan; Wang, Xin; Wang, Chengyu
Abstract: Materials for energy collection, conversion and storage are important for overcoming energy-shortage problems. The research reported a nanocomposite containing polyethylene-glycol-10000 (PEG10000) as phase-change-material composite (PCMC) and graphene nanosheets functionalized with Fe3 O4 nanoparticles (Fe3 O4 -GNS) stored and loaded into a porous carbonized-wood-flour (CWF) matrix. The Fe3 O4 -GNS/CWF/PCMC nanocomposite possessed favorable photothermal and magnetocaloric conversion properties. Introducing Fe3 O4 -GNS and CWF enhances the inherently low thermal conductivity of the PCMC. Energy was stored by the PCMC and released during the phase transition process. Furthermore, additional magnetothermal conversion and storage via Fe3 O4 -GNS component could reversely promote photothermal conversion due to continuous thermal energy supply. PEG10000 as biocompatible and nontoxic PCMC could form efficient combination within Fe3 O4 -GNS/CWF/PCMC and conduct least environmental-related effect. The nanocomposite exhibited favorable thermal conversion performance as temperature rising over 65 °C within 150 s, excellent thermal stability below 300 °C, a high melting enthalpy over 95 J/g and crystallization enthalpy over 85 J/g, good stability over 100 heating-cooling cycles, and efficient synergetic energy conversion. The PCMC with Fe3 O4 -GNS adsorbed in CWF rapidly converted light and magnetic energy to thermal energy, because of the enhanced thermal conductivity. The Fe3 O4 -GNS/CWF/PCMC nanocomposite therefore would have great potential in energy collecting, conversion and storage applications. Highlights: Magnetocaloric-assisted photothermal conversion and storage process. Biomass-derived and environmental materials function as function component. Thermal conducting enhancement and energy conversion promotion. High melting enthalpy over 95 J/g, crystallization enthalpy over 85 J/g of samples. Fast thermal conducting with thermal conductivity up to 0.225 W (m K) −1 of samples.